Practicing organization development : a guide for leading change - Rothwell, William J. (San Francisco California, 2010)
Completely revised, this new edition of the classic book offers contributions from experts in the field (Warner Burke, David Campbell, Chris Worley, David Jamieson, Kim Cameron, Michael Beer, Edgar Schein, Gibb Dyer, and Margaret Wheatley) and provides a road map through each episode of change facilitation. This updated edition features new chapters on positive change, leadership transformation, sustainability, and globalization. In addition, it includes exhibits, activities, instruments, and case studies, as well as an instructor's guide and supplemental materials on accompanying Website. This resource is written for OD practitioners, consultants, and scholars
Keywords: Business consultants Handbooks, manuals, etc; Academic theses; Business consultants